The dynamics of vertebrate homeobox gene evolution: gain and loss of genes in mouse and human lineages. - Zhong, Y; Holland, P; Zhong, Y (BioMed Central, 2011)
Background: Homeobox genes are a large and diverse group of genes, many of which play important roles in transcriptional regulation during embryonic development. Comparison of homeobox genes between species may provide insights into the evolution of developmental mechanisms. Results: Here we report an extensive survey of human and mouse homeobox genes based on their most recent genome assemblies, providing the first comprehensive analysis of mouse homeobox genes and updating an earlier survey of human homeobox genes. In total we recognize 333 human homeobox loci comprising 255 probable genes and 78 probable pseudogenes, and 324 mouse homeobox loci comprising 279 probable genes and 45 probable pseudogenes (accessible at http://homeodb.zoo.ox.ac.uk). Comparison to partial genome sequences from other species allows us to resolve which differences are due to gain of genes and which are due to gene losses. Conclusions: We find there has been much more homeobox gene loss in the rodent evolutionary lineage than in the primate lineage. While humans have lost only the Msx3 gene, mice have lost Ventx, Argfx, Dprx, Shox, Rax2, LOC647589, Tprx1 and Nanognb. This analysis provides insight into the patterns of homeobox gene evolution in the mammals, and a step towards relating genomic evolution to phenotypic evolution.